Cavitron ultrasonic surgical aspirator (CUSA) compared with conventional pancreatic transection in distal pancreatectomy: study protocol for the randomised controlled CUSA-1 pilot trial - Holze, Magdalena; Loos, Martin; Hüttner, Felix; Tenckhoff, Solveig; Feißt, Manuel; Knebel, Phillip; Klotz, Rosa; Mehrabi, Arianeb; Michalski, Christoph; Pianka, Frank (BMJ open, 2024)
Background Postoperative pancreatic fistula (POPF) remains the most common and serious complication after distal pancreatectomy. Many attempts at lowering fistula rates have led to unrewarding insignificant results as still up to 30% of the patients suffer from clinically relevant POPF. Therefore, the development of new innovative methods and procedures is still a cornerstone of current surgical research.The cavitron ultrasonic surgical aspirator (CUSA) device is a well-known ultrasound-based parenchyma transection method, often used in liver and neurosurgery which has not yet been thoroughly investigated in pancreatic surgery, but the first results seem very promising. - Methods The CUSA-1 trial is a randomised controlled pilot trial with two parallel study groups. This single-centre trial is assessor and patient blinded. A total of 60 patients with an indication for open distal pancreatectomy will be intraoperatively randomised after informed consent. The patients will be randomly assigned to either the control group with conventional pancreas transection (scalpel or stapler) or the experimental group, with transection using the CUSA device. The primary safety endpoint of this trial will be postoperative complications ≥grade 3 according to the Clavien-Dindo classification. The primary endpoint to investigate the effect will be the rate of POPF within 30 days postoperatively according to the ISGPS definition. Further perioperative outcomes, including postpancreatectomy haemorrhage, length of hospital stay and mortality will be analysed as secondary endpoints. - Discussion Based on the available literature, CUSA may have a beneficial effect on POPF occurrence after distal pancreatectomy. The rationale of the CUSA-1 pilot trial is to investigate the safety and feasibility of the CUSA device in elective open distal pancreatectomy compared with conventional dissection methods and gather the first data on the effect on POPF occurrence. This data will lay the groundwork for a future confirmatory multicentre randomised controlled trial. - Ethics and dissemination The CUSA-1 trial protocol was approved by the ethics committee of the University of Heidelberg (No. S-098/2022). Results will be published in an international peer-reviewed journal and summaries will be provided in lay language to study participants and their relatives. - Trial registration number DRKS00027474.
Gesehen am 03.06.2024